Near-alpha high-temperature titanium alloy suitable for 700 DEG C and preparation method thereof

By applying the cluster alloy design model in the Ti-Al-Zr-Nb-Ta-Si alloy system, a 700℃ high-temperature titanium alloy was designed and prepared, which solved the problems of low service temperature and poor damage tolerance of existing high-temperature titanium alloys, and achieved excellent performance of high-temperature strength and plasticity, and was suitable for high-temperature applications above 700℃.

CN119530613APending Publication Date: 2025-02-28DALIAN UNIV OF TECH
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411713462.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-27
Publication Date
2025-02-28

AI Technical Summary

Technical Problem

The existing high-temperature titanium alloys have low service temperatures, complex alloy elements and poor damage tolerance capabilities, making it difficult to meet the high-temperature application needs above 700℃.

Method used

A 700℃ high-temperature titanium alloy belonging to the Ti-Al-Zr-Nb-Ta-Si alloy system was designed. The main components include 7.5 wt.%~8.5 wt.%Al, 7 wt.%~12 wt.% Zr, 1.5 wt.%~3.5 wt.%Nb, 4 wt.%~6 wt.%Ta and 0.2 wt.%~0.6 wt.%Si, with the balance being Ti elements. The cluster alloy design model is used to guide the component design and synergistic change relationship. Through prefabricated high-melting point intermediate alloy blocks and vacuum arc smelting and other processes, a high-temperature titanium alloy with good high-temperature strength and plasticity was prepared.

Benefits of technology

The tensile strength at 700°C is achieved, the plasticity is not less than 40%, the temperature resistance reaches the level of titanium-based composite materials, and the preparation process is simple and the structure is stable, which is suitable as a preferred material for high-temperature structural components.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119530613A_ABST
    Figure CN119530613A_ABST
Patent Text Reader

Abstract

The invention relates to a near-alpha high-temperature titanium alloy suitable for 700 DEG C and a preparation method of the near-alpha high-temperature titanium alloy, and belongs to the technical field of high-temperature titanium alloys, the near-alpha high-temperature titanium alloy belongs to a Ti-Al-Zr-Nb-Ta-Si alloy system, the alloy comprises the following components in percentage by mass: 7.5-8.5 wt.% of Al, 7-12 wt.% of Zr, 1.5-3.5 wt.% of Nb, 4-6 wt.% of Ta, 0.2-0.6 wt.% of Si and the balance of Ti, and the components meet the following synergistic change relationship: Ti + 0.9 Zr is more than or equal to 79.7 wt.% and less than or equal to 84.7 wt.%, Al + Si is more than or equal to 7.8 wt.% and less than or equal to 8.8 wt.% The titanium alloy is high in zirconium content, free of tin, free of boron and free of rare earth elements, and is different from a core element of an existing high-temperature titanium alloy. Firstly, alloy is prepared after incoming material detection. Secondly, prefabricating a high-melting-point alloy block, and performing vacuum arc melting on the high-melting-point alloy block and the excess materials to prepare the alloy; and finally, aging treatment is carried out at 700 DEG C. The typical performance indexes under the casting condition are that the tensile strength at 600 DEG C is not lower than 800 MPa, the tensile strength at 700 DEG C is not lower than 600 MPa, the high-temperature strength and plasticity are good, the damage tolerance capacity is high, the structure is stable, and the technology is simple.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a 700°C high-temperature titanium alloy and a preparation method thereof, belonging to the technical field of high-temperature titanium alloys. Background Art

[0002] High-temperature titanium alloys have low density, excellent high-temperature strength and stability. They are widely used in aircraft engine compressors, afterburner barrels, blades and other components, and are the preferred material for reducing engine weight. Traditional high-temperature titanium alloys currently developed based on the Ti-Al-Sn-Zr-Mo-Si system, such as BT36, Ti60, IMI834, Ti1100, Ti600, Ti65, etc., have advantages such as good creep resistance, but their maximum service temperature is 600-650°C. For higher temperature compressor rear section materials, high-density nickel-based high-temperature alloys are usually used. The limitation of the use temperature seriously hinders the further application of high-temperature titanium alloys. Therefore, it is urgent to develop a 700°C high-temperature titanium alloy.

[0003] In the invention of CN110923589B, the Institute of Metal Research of the Chinese Academy of Sciences proposed a titanium alloy Ti-101AM that can withstand temperatures above 700°C. This method mainly involves adding a large amount of B element to the Ti-Al-Sn-Zr-Mo-Nb-Ta-Si alloy matrix to form TiB short fibers, but the TiB short fibers in the alloy are unevenly distributed, resulting in unstable high-temperature structure and performance of the alloy, a tensile strength of less than 780MPa at 600°C, and a large number of alloy elements. The preparation process is relatively complex and is not conducive to mass production and application.

[0004] In the invention of CN117535556A, Taiyuan University of Technology proposed a preparation method for a 700°C resistant micro-nano particle reinforced near-α high-temperature titanium alloy. The method mainly adds a high-melting-point W element to the Ti-Al-Sn-Zr-Mo-Nb-Si system, and regulates the size of the precipitated silicide and Ti3Al particles through repeated hot extrusion to improve the high-temperature performance of the alloy. However, the tensile strength of the alloy at 700°C is lower than 580MPa, and the preparation process is relatively complicated and not conducive to mass production and application.

[0005] To address the above problems, by introducing the cluster plus connected atom model that describes the near-order solid solution chemistry, the composition of mature industrial high-temperature titanium alloys was analyzed, and the near-order structural units and corresponding composition formulas of titanium alloys were found, which served as the basis for the composition design of high-temperature titanium alloys. Summary of the invention

[0006] The purpose of the present invention is to provide a high-temperature titanium alloy that can be used at 700°C. In order to solve the technical problems of low service temperature, complex alloy elements and poor damage tolerance of existing high-temperature titanium alloys, a high-temperature titanium alloy suitable for 700°C is designed and developed.

[0007] In order to achieve the above object, the technical solution adopted by the present invention is:

[0008] A high-temperature titanium alloy suitable for 700°C, the titanium alloy belongs to the Ti-Al-Zr-Nb-Ta-Si alloy system, the mass percentage of the main components is 7.5wt.% to 8.5wt.% Al, 7wt.% to 12wt.% Zr, 1.5wt.% to 3.5wt.% Nb, 4wt.% to 6wt.% Ta and 0.2wt.% to 0.6wt.% Si, the balance is Ti element; and the alloy elements satisfy the following synergistic variation relationship: 79.7wt.%≤Ti+0.9Zr≤84.7wt.%, 7.8wt.%≤Al+Si≤8.8wt.%, 7.5wt.%≤Ta+1.9Nb≤11.5wt.%, wherein Ti, Al and Ta are the main elements. The titanium alloy composition is high in zirconium and free of tin, boron and rare earth elements, which constitutes the core element difference from the existing high-temperature titanium alloy, and the given synergistic variation relationship of the components can more accurately guide the actual alloy production.

[0009] The mass purity of the titanium, aluminum, zirconium, niobium, tantalum and silicon is not less than 99.9%.

[0010] The 700°C high-temperature titanium alloy has good high-temperature strength and plasticity under casting conditions, the tensile strength at 700°C is not less than 600MPa, and the plasticity is not less than 40%. Its temperature resistance reaches the level of titanium-based composite materials, and the preparation process is simple and the structure is stable. It can be used as a preferred material for high-temperature structural components.

[0011] In addition, the present invention also provides a method for preparing a 700°C high temperature titanium alloy, comprising the following steps:

[0012] Step 1: Incoming material inspection

[0013] Inspect the surface quality, surface finish and oxidation state of each raw material;

[0014] Step 2: Alloy preparation

[0015] Calculate the mass of each component separately, weigh the mass of each component according to the ratio, and store the prepared alloy in a vacuum drying dish with a vacuum degree lower than 0.08MPa;

[0016] Step 3: Prefabricate high melting point master alloy blocks

[0017] All high melting point elements and a proper amount of titanium are heated to 2900-3250°C and subjected to vacuum arc melting for 10-15 minutes, and the melting is repeated 3-5 times to completely melt the alloy elements into alloy liquid, and then the alloy liquid is subjected to electromagnetic stirring and mixing for 5-8 minutes, and the furnace is cooled to room temperature to obtain a prefabricated high melting point intermediate alloy block; the high melting point elements are zirconium, silicon, niobium and tantalum; the mass percentage of the proper amount of titanium is 15%-30% of the total mass of the high melting point elements;

[0018] Step 4: Alloy preparation

[0019] The prefabricated high melting point intermediate alloy block obtained in step 3 is placed in the middle position of titanium and aluminum, heated to 2200-2500°C and subjected to vacuum arc melting for 10-15 minutes, and the melting is repeated 3-5 times to completely melt the alloy block into alloy liquid, and then the alloy liquid is electromagnetically stirred and mixed for 5-8 minutes, and then furnace cooled to room temperature to obtain a high-temperature titanium alloy. The prefabricated intermediate alloy block in step 3 can inhibit element segregation and improve organizational uniformity.

[0020] Step 5: Aging Process

[0021] The high temperature titanium alloy obtained in step 4 is sealed in a quartz tube, the quartz tube is vacuumized and filled with argon gas and then sealed, the sealed quartz tube is placed in a heat treatment furnace and heated to 650°C to 700°C and kept warm for 60 to 120 minutes, then the quartz tube is taken out, the quartz tube is crushed and directly air-cooled. The vacuum degree of the vacuum treatment is less than 0.02MPa.

[0022] Step 6: Organization analysis and performance testing

[0023] The microstructure analysis and mechanical property testing of the high-temperature titanium alloy after aging treatment obtained in step five are performed.

[0024] The design principle and innovative analysis of the present invention are as follows: the above technical scheme is adopted to implement alloy composition design according to the cluster alloy design model, which gives chemical near-program structure units and corresponding composition formulas. The alloy elements first construct stable solid solution structure units with the matrix titanium element. The present invention analyzes the cluster composition formula of the mature industrial high-temperature titanium alloy IMI834 and obtains the cluster alloy composition design model structure units of α, β and silicide phases, which are: and The element symbol with an upper horizontal line represents an alloying element similar to the element, such as Al-like elements that stabilize the α phase. Elements similar to the matrix Ti Stable β The ratio of α, β and silicide cluster units is 16.7:1:0.3. The introduction of α, β solid solution phase and silicide composition formula provides a basis for understanding the existing near-α high-temperature titanium alloy and designing high-performance high-temperature titanium alloy composition.

[0025] The present invention designs a process of 700°C high temperature titanium alloy as follows:

[0026] 1) In order to improve the high temperature strength of the alloy, the main alloying elements are Al, Si and Zr, and Al is used to replace Sn in the IMI834 alloy cluster formula, because aluminum contributes more to high temperature strength and can improve the alloy's oxidation resistance. Silicon can improve the alloy's high temperature creep resistance; zirconium is infinitely soluble in both α and β phases, which can improve the alloy's high temperature strength through solid solution strengthening; but when the aluminum content exceeds 9.0wt.%, it is easy to form a brittle phase Ti3Al, resulting in reduced alloy plasticity; when the silicon content exceeds 1.5wt.%, it is easy to form coarse silicides, resulting in reduced alloy plasticity; when the zirconium content exceeds 12.5wt.%, the alloy's oxidation resistance is reduced;

[0027] 2) In order to increase the thermal stability and plasticity of the alloy melt, the main alloying elements are refractory metals such as Ta and Nb. Refractory metals can improve the thermal stability of the melt, and have a body-centered cubic crystal structure and a slip system that can increase plasticity. However, if the content of a single refractory metal exceeds 6.5wt.% or the total amount exceeds 15wt.%, it is easy to produce brittle phases and alloy spots.

[0028] 3) By changing the ratio of Ti, Al, Zr, Nb, Ta and Si in the cluster formula, the best multi-element alloying effect is produced, so that the thermal stability of the melt is optimized. Finally, the mass percentage of the main components of the 700°C high temperature titanium alloy is determined to be 7.5wt.% to 8.5wt.% Al, 7wt.% to 12wt.% Zr, 1.5wt.% to 3.5wt.% Nb, 4wt.% to 6wt.% Ta and 0.2wt.% to 0.6wt.% Si, and the remainder is Ti element and other inevitable impurities.

[0029] Compared with the invention in CN116770130A, a 700°C high-temperature titanium alloy for aircraft engines proposed by the Beijing Institute of Aeronautical Materials of AECC has the following components and mass percentages: Al: 5.5wt.%~7.0wt.%, Sn: 3.0wt.%~5.0wt.%, Hf: 2.0wt.%~4.5wt.%, Mo: 0.0wt.%~1.0wt.%, Si: 0.5wt.%~0.7wt.%, Nb: 0.2wt.%~0.5wt.%, Ta: 3.5wt.%~4.5wt.%, W: 0.6wt.%~1.2wt.%, C: 0.04wt.%~0.08wt.%, O≤0.15wt.%, Fe≤0.015wt.%, and the remainder is Ti element and other inevitable impurities. The 700°C high-temperature titanium alloy described in the present invention is different from the comparative patent in the following three aspects: 1) The types of alloying elements are simple, with only 6 main alloying elements: Ti, Al, Zr, Nb, Ta and Si, and no tin, hafnium, molybdenum and tungsten elements; 2) The high zirconium content produces a strong solid solution strengthening effect, showing better high-temperature strength; 3) The range of Al, Nb and Si elements completely exceeds that of the comparative patent; 4) The introduction of a composition synergistic change control scheme derived from a cluster model is conducive to accurately guiding actual alloy production.

[0030] The beneficial effects of the present invention are:

[0031] 1) The present invention provides a 700℃ high temperature titanium alloy, wherein higher Al, Zr and Si can improve the high temperature strength of the alloy, and appropriate amounts of Nb and Ta can enhance the thermal stability and plasticity of the melt, and the synergistic change relationship of the elements is given according to the cluster composition design method, which is beneficial to the composition control of actual production; 2) The prefabricated high melting point intermediate alloy block can inhibit the uneven dissolution of elements and improve the uniformity of the organization; 3) The characteristic is that it is high in zirconium and does not contain tin elements and carbon, boron and rare earth elements that are easy to cause uneven organization and high temperature brittleness. The typical performance indicators in the cast state are: the tensile strength at 600℃ is not less than 800MPa, the plasticity is not less than 15%, the tensile strength at 700℃ is not less than 600MPa, and the plasticity is not less than 40%, reaching the level of titanium-based composite materials, and the preparation process is simple, the organization is uniform, and it has good high temperature strength and plasticity, high damage tolerance, high reliability, and low cost, which is convenient for large-scale production and can be used as an alternative material for cutting-edge high temperature structural components. BRIEF DESCRIPTION OF THE DRAWINGS

[0032] Figure 1 It is a schematic diagram of the electromagnetic stirring system device used for preparing the prefabricated master alloy block and alloy in steps three and four of the specific implementation mode one;

[0033] Figure 2 is a microstructure diagram of the high temperature titanium alloy prepared in Example 1;

[0034] Figure 3 is a microstructure diagram of the high temperature titanium alloy prepared in Example 2;

[0035] Figure 4 is a microstructure diagram of the high temperature titanium alloy prepared in Example 3;

[0036] Figure 5 This is a microstructure diagram of the high-temperature titanium alloy of Example 1 without prefabricated high-melting-point alloy block.

[0037] In the figure: 1 sealed chamber, 2 robotic arm, 3 welding machine heat source emitter, 4 tungsten pole head, 5 copper mold, 6 electromagnetic emitter. DETAILED DESCRIPTION

[0038] The technical solution of the present invention is further described in detail below through the drawings and embodiments.

[0039] The electromagnetic stirring system device used for preparing the prefabricated master alloy block and alloy in steps 3 and 4 of this embodiment is as follows: Figure 1 As shown, it is composed of a sealed chamber 1, a mechanical arm 2, a welding machine heat source emitter 3, a tungsten pole head 4, a copper mold 5 and an electromagnetic emitter 6; the mechanical arm 2, the welding machine heat source emitter 3, the tungsten pole head 4, the copper mold 5 and the electromagnetic emitter 6 are arranged inside the sealed chamber 1, the welding machine heat source emitter 3 is arranged on the lower end surface of the mechanical arm 2 and is sealed and slidably connected, the lower end surface of the welding machine heat source emitter 3 and the tungsten pole head 4 are fixed, the copper mold 5 is arranged on the upper end surface of the electromagnetic emitter 6 and is sealed and slidably connected, and the tungsten pole head 4 is located above the copper mold 5. The method of using the device is as follows: fill the alloy elements into the copper mold 5, then evacuate the sealed chamber 1 and fill it with argon gas, then start the welding machine heat source emitter 3 to control the current of the tungsten pole head 4, and then use the tungsten pole head 4 to generate arc heat to heat and melt the alloy elements in the copper mold 5, so that the alloy elements are completely melted into a mixed liquid, and then start the electromagnetic emitter 6 to electromagnetically stir and mix the alloy liquid in the copper mold 5. The function of the copper mold 5 is to limit the downward flow of the slurry when electromagnetic stirring is applied. The argon gas is filled in order to prevent the material from oxidizing and failing, so as to obtain a prefabricated titanium alloy ingot. The device adopts a program-controlled mechanical arm 2 so that the welding machine heat source emitter 3 and the tungsten pole head 4 can move synchronously.

[0040] Embodiment 1:

[0041] The present embodiment is a titanium alloy resistant to high temperature of 700°C, and the mass percentage (wt.%) of each element is Al: 7.5wt.%, Zr: 12wt.%, Ta: 4.0wt.%, Nb: 3.5wt.%, Si: 0.6wt.%, and the remainder is Ti element and other inevitable impurities, corresponding to the lower limit of the main element content and the upper limit of the content of other elements within a given synergistic variation range; the mass purity of the aluminum, zirconium, tantalum, niobium, silicon and titanium is 99.98%.

[0042] This embodiment is a method for preparing a 700°C high temperature resistant titanium alloy, which is specifically carried out according to the following steps:

[0043] Step 1: Incoming material inspection: The surface quality of raw materials is qualified, the surface finish is qualified, and there is no oxidation;

[0044] Step 2: Alloy preparation: Calculate the mass of each component, weigh each component according to the ratio, and store the prepared alloy in a vacuum drying dish with a vacuum degree of 0.06 MPa;

[0045] Step 3, prefabricating a high melting point master alloy block: heating all niobium, tantalum, zirconium, silicon and an appropriate amount of titanium to 3250°C for 15 minutes of vacuum arc melting, and then turning the melting for 5 times to completely melt the alloy elements into alloy liquid, and then electromagnetically stirring and mixing the alloy liquid for 5 minutes, and then furnace cooling to room temperature to obtain a prefabricated high melting point master alloy block; the mass percentage of the appropriate amount of titanium is 15% of the total mass of the high melting point elements;

[0046] Step 4, alloy preparation: place the prefabricated high melting point intermediate alloy block obtained in step 3 in the middle position of titanium and aluminum, heat to 2200°C for 10 minutes for vacuum arc melting, repeat the melting 3 times to make the alloy block completely melt into alloy liquid, then electromagnetically stir and mix the alloy liquid for 5 minutes, and then cool it to room temperature in the furnace.

[0047] Step 5, aging treatment: The high-temperature titanium alloy obtained in step 4 is sealed in a quartz tube, the quartz tube is vacuumed and filled with argon gas and then sealed, the sealed quartz tube is placed in a heat treatment furnace and heated to 650°C for 60 minutes, then the quartz tube is taken out, the quartz tube is crushed and directly air-cooled to obtain the high-temperature titanium alloy. The vacuum degree of the vacuum treatment is 0.01MPa.

[0048] Step 6. Organization analysis and performance testing: Conduct microstructure analysis and tensile mechanical property testing on high-temperature titanium alloy.

[0049] The alloy microstructure and structure after aging treatment were detected by OM and SEM. The results showed that the alloy exhibited a basket-like structure, silicide particles precipitated on the α / β interface, and no other harmful phases precipitated. See attached Figure 2The tensile properties at room temperature, 600°C, 650°C, 700°C and 750°C were measured using an MTS universal tensile testing machine: room temperature yield strength σ s =1030MPa, tensile strengthσ b =1127MPa, elongation after fracture δ = 9.4%; yield strength σ at 600℃ s =621MPa, tensile strengthσ b =805MPa, elongation after fracture δ = 15.6%; yield strength σ at 650℃ s =576MPa, tensile strengthσ b =729MPa, elongation after fracture δ = 30.4%; yield strength σ at 700℃ s =506MPa, tensile strengthσ b =613MPa, elongation after fracture δ = 41.4%; yield strength σ at 750℃ s =391MPa, tensile strengthσ b =445MPa, elongation after break δ=51.4%.

[0050] Embodiment 2: This embodiment is a titanium alloy resistant to high temperature of 700°C. The mass percentage (wt.%) of each component in the titanium alloy is Al: 8wt.%, Zr: 9.5wt.%, Nb: 2.5wt.%, Ta: 5wt.%, Si: 0.4wt.%, and the remainder is Ti element and other inevitable impurities, corresponding to the median content of each element within a given synergistic variation range; the mass purity of the aluminum, zirconium, niobium, tantalum, silicon and titanium is 99.98%.

[0051] This embodiment is a method for preparing a 700°C high temperature titanium alloy, which is specifically carried out according to the following steps:

[0052] Step 1: Incoming material inspection: The surface quality of raw materials is qualified, the surface finish is qualified, and there is no oxidation;

[0053] Step 2: Alloy preparation: Calculate the mass of each component, weigh each component according to the ratio, and store the prepared alloy in a vacuum drying dish with a vacuum degree of 0.07 MPa;

[0054] Step 3, prefabricating a high melting point master alloy block: heating the high melting point elements and an appropriate amount of titanium to 3100°C for 12 minutes of vacuum arc melting, and then repeatedly melting for 4 times to completely melt the alloy elements into an alloy liquid, and then subjecting the alloy liquid to electromagnetic stirring and mixing for 6 minutes, and then furnace cooling to room temperature to obtain a prefabricated high melting point master alloy block; the high melting point elements are zirconium, niobium, tantalum and silicon; the mass percentage of the appropriate amount of titanium is 20% of the total mass of the high melting point elements;

[0055] Step 4, alloy preparation: place the prefabricated high melting point intermediate alloy block obtained in step 3 in the middle position of titanium and aluminum, heat to 2350°C for 12 minutes of vacuum arc melting, repeat the melting 4 times, make the alloy block completely melt into alloy liquid, then electromagnetically stir and mix the alloy liquid for 6 minutes, and then cool it to room temperature in the furnace.

[0056] Step 5, aging treatment: the alloy obtained in step 4 is sealed in a quartz tube, the quartz tube is vacuumed and filled with argon gas and then sealed, the sealed quartz tube is placed in a heat treatment furnace and heated to 680°C for 90 minutes, then the quartz tube is taken out, the quartz tube is crushed and directly air-cooled to obtain a high-temperature titanium alloy. The vacuum degree of the vacuum treatment is 0.015MPa.

[0057] Step 6. Organization analysis and performance testing: Conduct microstructure analysis and tensile mechanical property testing on high-temperature titanium alloy.

[0058] The alloy microstructure and structure after aging treatment were detected by OM and SEM. The results showed that the alloy exhibited a basket-like structure, silicide particles precipitated on the α / β interface, and no other harmful phases precipitated. See attached Figure 3 The tensile properties at room temperature, 600°C, 650°C, 700°C and 750°C were measured using an MTS universal tensile testing machine: room temperature yield strength σ s =1083MPa, tensile strengthσ b =1194MPa, elongation after fracture δ = 5.6%; yield strength σ at 600℃ s =621MPa, tensile strengthσ b =833MPa, elongation after fracture δ = 15.9%; yield strength σ at 650℃ s =588MPa, tensile strengthσ b =769MPa, elongation after fracture δ = 27.5%; yield strength σ at 700℃ s =522MPa, tensile strengthσ b =619MPa, elongation after fracture δ = 40.6%; yield strength σ at 750℃ s =369MPa, tensile strength σ b =445MPa, elongation after break δ=55.4%.

[0059] Embodiment 3: This embodiment is a 700℃ high-temperature titanium alloy, and the mass percentage (wt.%) of each component in the titanium alloy is Al: 8.5wt.%, Zr: 7wt.%, Nb: 1.5wt.%, Ta: 6wt.%, Si: 0.2wt.%, and the remainder is Ti element and other inevitable impurities, corresponding to the upper limit of the main element content and the lower limit of the content of other elements within a given synergistic variation range; the mass purity of the aluminum, zirconium, niobium, tantalum, silicon and titanium is 99.98%.

[0060] This embodiment is a method for preparing a 700°C high temperature titanium alloy, which is specifically carried out according to the following steps:

[0061] Step 1: Incoming material inspection: The surface quality of raw materials is qualified, the surface finish is qualified, and there is no oxidation;

[0062] Step 2: Alloy preparation: Calculate the mass of each component, weigh each component according to the ratio, and store the prepared alloy in a vacuum drying dish with a vacuum degree of 0.05 MPa;

[0063] Step 3, prefabricating a high melting point master alloy block: heating the high melting point elements and an appropriate amount of titanium to 2900°C for 10 minutes of vacuum arc melting, and then repeatedly melting for 3 times to completely melt the alloy elements into an alloy liquid, and then subjecting the alloy liquid to electromagnetic stirring and mixing for 8 minutes, and then furnace cooling to room temperature to obtain a prefabricated high melting point master alloy block; the high melting point elements are zirconium, niobium, tantalum and silicon; the mass percentage of the appropriate amount of titanium is 30% of the total mass of the high melting point elements;

[0064] Step 4, alloy preparation: place the prefabricated high melting point intermediate alloy block obtained in step 3 in the middle position of titanium and aluminum, heat to 2500°C for 15 minutes for vacuum arc melting, repeat the melting 5 times to make the alloy block completely melt into alloy liquid, then electromagnetically stir and mix the alloy liquid for 8 minutes, and then cool it to room temperature in the furnace.

[0065] Step 5, aging treatment: the alloy obtained in step 5 is sealed in a quartz tube, the quartz tube is vacuumed and filled with argon gas and then sealed, the sealed quartz tube is placed in a heat treatment furnace and heated to 700°C and kept for 120 minutes, then the quartz tube is taken out, the quartz tube is crushed and directly air-cooled to obtain a high-temperature titanium alloy. The vacuum degree of the vacuum treatment is 0.01MPa.

[0066] Step 6. Organization analysis and performance testing: Conduct microstructure analysis and tensile mechanical property testing on high-temperature titanium alloy.

[0067] The alloy microstructure and structure after aging treatment were detected by OM and SEM. The results showed that the alloy exhibited a basket-like structure, silicide particles precipitated on the α / β interface, and no other harmful phases precipitated. See attached Figure 4 The tensile properties at room temperature, 600°C, 650°C, 700°C and 750°C were measured using an MTS universal tensile testing machine: room temperature yield strength σ s =1152MPa, tensile strengthσ b =1239MPa, elongation after fracture δ = 3.6%; yield strength σ at 600℃ s =659MPa, tensile strengthσ b =880MPa, elongation after fracture δ = 16.1%; yield strength σ at 650℃ s =607MPa, tensile strengthσ b =792MPa, elongation after fracture δ = 22.6%; yield strength σ at 700℃ s =506MPa, tensile strengthσ b =653MPa, elongation after fracture δ = 46.6%; yield strength σ at 750℃ s =342MPa, tensile strength σ b =420MPa, elongation after break δ=52.6%.

[0068] Comparative Example 1: The difference from Example 1 is that no prefabricated master alloy block is prepared, and the alloy elements are directly subjected to vacuum arc melting. The rest is the same as Example 2. Figure 2 This is an optical microstructure diagram of the high-temperature ultra-high-strength titanium alloy prepared in Example 1. As shown in the figure, the sample has a uniform microstructure and a dense structure. Figure 5 This is an optical microstructure diagram of the titanium alloy prepared in Example 2 without preparing a prefabricated master alloy block. As shown in the figure, the sample microstructure is uneven, silicides are segregated, and there are micropores and the structure is not dense.

[0069] Compared with a high temperature titanium alloy for high temperature of 600℃ proposed in patent CN113046595A, the tensile strength at 600℃ is 660MPa, which shows that the tensile strength at 600℃ of the high temperature ultra-high strength titanium alloy prepared in Example 1 is increased by more than 20%. Compared with a high temperature resistant titanium alloy at 700℃ proposed in patent CN113249614A, the tensile strength at 700℃ is 536MPa, the yield strength is 490MPa, and the elongation is 30.4%, which shows that the tensile strength at 700℃ of the high temperature ultra-high strength titanium alloy prepared in Example 1 is increased by more than 14%, and the elongation is basically the same. At temperatures of 600℃ and above, the alloy prepared in Example 1 has very excellent high temperature strength and reliability, and can be used as a preferred material for high temperature structural components.

[0070] The above-described embodiments merely express the implementation methods of the present invention, but they cannot be understood as limiting the scope of the patent of the present invention. It should be pointed out that for those skilled in the art, several modifications and improvements can be made without departing from the concept of the present invention, which all belong to the protection scope of the present invention.

Claims

1. A near-α high temperature titanium alloy suitable for 700°C, characterized in that: The near-α high-temperature titanium alloy suitable for 700° C. belongs to the Ti-Al-Zr-Nb-Ta-Si alloy system, and its main alloy components are Ti, Al, Zr, Nb, Ta, Si and other impurity elements.

2. The near-α high temperature titanium alloy suitable for 700°C according to claim 1, characterized in that: The main alloy components are 7.5wt.% to 8.5wt.% Al, 7wt.% to 12wt.% Zr, 1.5wt.% to 3.5wt.% Nb, 4wt.% to 6wt.% Ta and 0.2wt.% to 0.6wt.% Si in percentage by mass, and the balance is Ti element.

3. The near-α high temperature titanium alloy suitable for 700°C according to claim 2, characterized in that: The alloy composition is defined by the following synergistic variation relationship: 79.7wt.%≤Ti+0.9Zr≤84.7wt.%, 7.8wt.%≤Al+Si≤8.8wt.%, 7.5wt.%≤Ta+1.9Nb≤11.5wt.%.

4. The near-α high temperature titanium alloy suitable for 700°C according to claim 1, characterized in that: The high-strength titanium alloy suitable for 700°C has typical properties: room temperature yield strength>1030MPa, room temperature tensile strength>1100MPa, room temperature elongation>5%, tensile strength>800MPa at 600°C, and tensile strength>600MPa at 700°C.

5. A method for preparing a near-α high temperature titanium alloy suitable for 700°C according to any one of claims 1 to 4, characterized in that: The following steps are involved: Step 1: Incoming material inspection: Check the surface quality, finish and oxidation state of each raw material; Step 2: alloy preparation, calculate the mass of each component, weigh the mass of each component according to the ratio, and store the prepared alloy in a vacuum drying dish; Step 3, prefabricating a high melting point alloy block, subjecting the high melting point element and titanium to vacuum arc melting, repeatedly melting for multiple times, so that the alloy element is completely melted into alloy liquid, then electromagnetic stirring and mixing are performed, and then furnace cooling is performed to room temperature to obtain a prefabricated high melting point intermediate alloy block; Step 4, alloy preparation, placing the prefabricated high melting point master alloy block obtained in step 3 at the middle position of titanium and aluminum for vacuum arc melting, repeatedly melting for multiple times, so that the alloy block is completely melted into alloy liquid, then electromagnetic stirring and mixing are performed, and then furnace cooling is performed to room temperature; Step five, subjecting the high temperature titanium alloy obtained in step four to high temperature aging treatment to obtain a high temperature titanium alloy.

6. The method for preparing a near-α high temperature titanium alloy suitable for 700°C according to claim 5, characterized in that: The step five is specifically as follows: the high-temperature titanium alloy obtained in step four is sealed in a quartz tube, the quartz tube is vacuumed and filled with argon and then sealed, the quartz tube is kept at 650°C to 700°C for 60 to 120 minutes, then taken out, the quartz tube is crushed and directly air-cooled to obtain the high-temperature titanium alloy.

7. The method for preparing a near-α high temperature titanium alloy suitable for 700°C according to claim 6, characterized in that: The vacuum degree of the vacuum treatment in step 5 is lower than 0.02MPa.

8. The method for preparing a near-α high temperature titanium alloy suitable for 700°C according to claim 5, characterized in that: In the step 2, the high melting point elements are zirconium, silicon, niobium and tantalum; the mass percentage of titanium is 15% to 30% of the total mass of the high melting point elements.

9. The method for preparing a near-α high temperature titanium alloy suitable for 700°C according to claim 5, characterized in that: The vacuum degree in the step 2 is lower than 0.08 MPa.

10. The method for preparing a near-α high temperature titanium alloy suitable for 700°C according to claim 5, characterized in that: In the step three, after the alloy elements are completely melted into alloy liquid, the electromagnetic stirring time is 5 min to 8 min; in the step four, after the alloy elements are completely melted into alloy liquid, the electromagnetic stirring time is 5 min to 8 min.

Citation Information

Patent Citations

  • A short fiber reinforced high-temperature titanium alloy Ti-101AM for 700–750℃

    CN110923589B

  • Titanium alloy resistant to high temperature of 700 DEG C and preparation method thereof

    CN113249614A

  • Titanium alloy resistant to high temperature of 700 DEG C for aero-engine and preparation method of titanium alloy

    CN116770130A

  • Preparation method of 700 DEG C-resistant micro-nano particle reinforced near-alpha high-temperature titanium alloy

    CN117535556A